2020
DOI: 10.1073/pnas.2000153117
|View full text |Cite
|
Sign up to set email alerts
|

Distemper, extinction, and vaccination of the Amur tiger

Abstract: Canine distemper virus (CDV) has recently emerged as an extinction threat for the endangered Amur tiger (Panthera tigris altaica). CDV is vaccine-preventable, and control strategies could require vaccination of domestic dogs and/or wildlife populations. However, vaccination of endangered wildlife remains controversial, which has led to a focus on interventions in domestic dogs, often assumed to be the source of infection. Effective decision making requires an understanding of the true reservoir dynamics, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(81 citation statements)
references
References 39 publications
(46 reference statements)
0
76
3
Order By: Relevance
“…Our simulation results found that relatively high levels of vaccination were required to reduce impacts of FeLV in panthers, in contrast to studies in other endangered species (7, 9). However, here we are investigating a pathogen with a long duration of infectiousness and lack the advantages of distinct corridors between panther sub-populations for reducing required levels of vaccination.…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…Our simulation results found that relatively high levels of vaccination were required to reduce impacts of FeLV in panthers, in contrast to studies in other endangered species (7, 9). However, here we are investigating a pathogen with a long duration of infectiousness and lack the advantages of distinct corridors between panther sub-populations for reducing required levels of vaccination.…”
Section: Discussioncontrasting
confidence: 92%
“…Our simulation results found that relatively high levels of vaccination were required to reduce impacts of FeLV in panthers, in contrast to studies in other endangered species (7,9).…”
Section: Limitations and Future Directionscontrasting
confidence: 90%
See 2 more Smart Citations
“…Spillover may result in catastrophic consequences to the new host, resulting in significant economic [4,5] or conservation [6][7][8][9] impacts and major threats to wildlife survival and biodiversity; for example, distemper in African lions (Panthera leo) [10], and plague and distemper in blackfooted ferrets (Mustela nigripes) [11,12]. Recent studies have indicated, however, that crossspecies transmission frequently occurs without substantial population-level impacts to the recipient host [13,14].…”
Section: Outcomes Of Spillover Transmissionmentioning
confidence: 99%